Status kesehatan mulut dan asupan makan sebagai faktor risiko underweight pada lansia - Dian Isti Angraini; Al Supartinah; Deddy Nur Wachid (Jurnal Gizi Klinik Indonesia, 2013)
Background: Oral health status and dietary intake contribute to nutritional status in elderly. Missing teeth cause chewing disorder that reduces quality and quantity of food intake, which finally makes the elderly have underweight nutritional status.Objective: To determine the risk factors for underweight in the elderly at Yogyakarta Municipality.Method: The study was observational with case control design on elderly at Yogyakarta Municipality. Subjects consisted of 210 elderly matched in age and gender. Sampling was done by multistage random sampling. Oral health status was assessed through dental health status (index of missing teeth) and periodontal status (gingival index, periodontal index and oral hygiene index), dietary intake was collected by using semi quantitative food frequency questionnaire (SQ-FFQ) and underweight nutritional status was based on body mass armspan (BMA). Data were analyzed by using tests of X2 Mc.Nemar, X2 Stuart Maxwell, and conditional logistic regression.Results: Bivariate analysis showed the number of missing teeth ≥ 21 (OR=3.67, p<0.05) and 16-20 (OR=3.53, p<0.05) as risk factors of underweight, whereas the gingival index, periodontal index and oral hygiene index were not. Less intake of energy (OR=6.3), protein (OR=7.83), fat (OR=5.67) and carbohydrates (OR=7.5) were risk factors of underweight (p<0.01). Income less than Rp 808.000,00 was also risk factor for underweight (OR=4.5; p<0.01). Multivariate analysis showed the significant risk factors for underweight were the missing teeth ≥ 21 (OR=8.76) and 16-20 (OR=6.04) which increased by income less than Rp 808.000,00 (OR=5.94), less fat intake (OR=4.88), and less carbohydrate intake (OR=5.48). Income was confounding factor in the risk of missing teeth and protein intake for becoming underweight.Conclusion: Significant risk factors of underweight in elderly were missing teeth ≥ 16, less intake of fat and carbohydrate, and income less than Rp 808.000,00.